Review on natural ester and nanofluids as an environmental friendly alternative to transformer mineral oil. Issue 2 (15th May 2020) - Jacob, Joyce; Preetha, P.; Thiruthi Krishnan, Sindhu
Abstract : The development of reliable, environmentally safe and economic insulating oil for the transformer is an endless effort of the electrical industry. Recent research is based on natural ester fluid, the green insulating oil which exhibits excellent dielectric performance and environment friendly characteristics. Nanofluids are also emerging as potential replacement for the conventional mineral oil used in transformers. Characterisation of nanoparticle filled mineral oil and natural esters have validated their improved dielectric behaviour in comparison to the unfilled oil. Although the applications are wide, the state of the art technology requires a deeper understanding of the underlying phenomenon. Much work is expected to be done in the application of nanofluids prepared with mineral oil and natural ester, particularly its effect on the cellulose insulation. The study provides an overview of the different materials that have been used as alternatives to the conventional transformer mineral oil, with special emphasis on natural esters and natural ester nanofluids, their advantages and challenges.